2006
DOI: 10.1097/01.brs.0000250076.74366.9d
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain Patients Demonstrate Increased Hip Extensor Muscle Activity During Standardized Submaximal Rotation Efforts

Abstract: This study provided evidence of increased muscle recruitment in CLBP patients when performing a standardized trunk rotation task. These results may have implications for the design of therapeutic exercise programs for CLBP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
1
17
2
1
Order By: Relevance
“…Panjabi (1992) proposed that an alteration of the passive structures may be related to a decrease in the intrinsic stiffness that can then lead to increased muscular activity as a compensatory response in order to sustain the stability of the trunk. This was confirmed by several studies which revealed evidence of increased activities of the trunk muscles due to low back pain (LBP) (Fischer and Chang, 1985;Pirouzi et al, 2006). Increased muscle co-contractions (Granata and Marras, 1995;Marras et al, 2004;Radebold et al, 2000) have also been observed, and may be related to increased spinal stress (Granata and Marras, 1995;Marras et al, 2004) that may lead to injuries and spinal degeneration (Adams et al, 1996;Gallagher et al, 2005).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Panjabi (1992) proposed that an alteration of the passive structures may be related to a decrease in the intrinsic stiffness that can then lead to increased muscular activity as a compensatory response in order to sustain the stability of the trunk. This was confirmed by several studies which revealed evidence of increased activities of the trunk muscles due to low back pain (LBP) (Fischer and Chang, 1985;Pirouzi et al, 2006). Increased muscle co-contractions (Granata and Marras, 1995;Marras et al, 2004;Radebold et al, 2000) have also been observed, and may be related to increased spinal stress (Granata and Marras, 1995;Marras et al, 2004) that may lead to injuries and spinal degeneration (Adams et al, 1996;Gallagher et al, 2005).…”
Section: Introductionmentioning
confidence: 63%
“…In comparison with the standing model used in previous studies (Cholewicki et al, 1997;Pirouzi et al, 2006;Sihvonen et al, 1991;Silfies et al, 2005), the present study employed a sitting position to study trunk balance as it would allow us to remove the influence of the legs and to study the role of the trunk in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that trunk muscle activities increases during lifting and trunk rotation in CLBP patients. 8,9 It seems that increased activity of the trunk muscles can be due to abnormal motor recruitment patterns. 3 Stokes et al 10 reported that increased superficial trunk muscle activation was due to a "painadaptation" hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Since in the past subcategorizing on a structural basis was found to be fruitless, present research predominantly aims at subcategorization based on functional analysis. [1][2][3][4][5][6][7][8][9][10][11] For successful functional subcategorization, both an adequate parameter and a preliminary subclassification preferably based on a "gold standard" are essential. This study aims at subcategorizing 2 back pain groups using forward bending as a discriminating tool.…”
mentioning
confidence: 99%